Hospitalists as Triagists: Description of the Triagist Role across Academic Medical Centers. Issue 2 (23rd October 2019) - Velásquez, Sadie Trammell; Wang, Emily S; White, Andrew A; Chadha, Jagriti; Mader, Michael; Leykum, Luci K; Pugh, Jacqueline
Abstract : From the hospitalist perspective, triaging involves the evaluation of a patient for potential admission to an inpatient service. Although traditionally done by residents, many academic hospitalist groups have assumed the responsibility for triaging. We conducted a cross‐sectional survey of 235 adult hospitalists at 10 academic medical centers (AMCs) to describe the similarities and differences in the triagist role and assess the activities and skills associated with the role. Eight AMCs have a defined triagist role; at the others, hospitalists supervise residents/advanced practice providers. The triagist role is generally filled by a faculty physician and shared by all hospitalists. We found significant variability in verbal communication practices ( P = .02) and electronic communication practices ( P < .0001) between the triagist and the current provider (eg, emergency department, clinic provider), and in the percentage of patients evaluated in person ( P < .0001). Communication skills, personal efficiency, and systems knowledge are dominant themes of attributes of an effective triagist.